Nuclear structures surrounding internal lamin invaginations - Legartová, Soňa; Stixová, Lenka; Laur, Oskar; Kozubek, Stanislav; Sehnalová, Petra; Bártová, Eva (Journal of cellular biochemistry, 2014)
A- and C-type lamins are intermediate filament proteins responsible for the maintenance of nuclear shape and most likely nuclear architecture. Here, we propose that pronounced invaginations of A/C-type lamins into the nuclear interior represent channels for the transport of regulatory molecules to and from nuclear and nucleolar regions. Using fluorescent protein technology and immunofluorescence, we show that A-type lamin channels interact with several nuclear components, including fibrillarin- and UBF-positive regions of nucleoli, foci of heterochromatin protein 1 β, polycomb group bodies, and genomic regions associated with DNA repair. Similar associations were observed between A/C-type lamin channels and nuclear pores, lamin-associated protein LAP2α, and promyelocytic leukemia nuclear bodies. Interestingly, regions with high levels of A/C-type lamins had low levels of B-type lamins, and vice versa. These characteristics were observed in primary and immortalized mouse embryonic fibroblasts as well as human and mouse embryonic stem cell colonies exhibiting stem cell-specific lamin positivity. Our findings indicate that internal channels formed by nuclear lamins likely contribute to normal cellular processes through association with various nuclear and nucleolar structures.
Keywords: Membrane Proteins; DNA-Binding Proteins; Lamin Type B; Humans; chromozomální proteiny, nehistonové; Cell Nucleus; DNA vazebné proteiny; oprava DNA; lamin typ B; buněčné jádro; lidé; zvířata; myši; Mice; DNA Repair; Chromosomal Proteins, Non-Histone; Lamin Type A; membránové proteiny; Animals; lamin typ A